2012
DOI: 10.1074/jbc.m111.333856
|View full text |Cite
|
Sign up to set email alerts
|

CtBP-interacting BTB Zinc Finger Protein (CIBZ) Promotes Proliferation and G1/S Transition in Embryonic Stem Cells via Nanog

Abstract: Background: G1/S transition is important for embryonic stem cell (ESC) proliferation; however, the transcriptional factor that regulates this remains largely unknown. Results: CIBZ, a transcription factor, regulates ESC proliferation and G1/S transition. Conclusion: CIBZ-associated ESC proliferation and G1/S transition is dependent on Nanog expression. Significance: This study provides insights into the mechanism underlying the rapid proliferation and G1/S transition of ESCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 33 publications
6
30
1
Order By: Relevance
“…Noxa and Puma, their expression levels were decreased in Zbtb38 lentivirus-treated SCI mice from day 4 after injection, whereas Bak expression was only significantly lower on the days 2 of testing when Zbtb38 expression was rescued (Figure 5 ). Zbtb38 has been implicated to promote proliferation and G1/S transition in mouse embryonic stem cells [ 24 ]. We next determined cell cycle with or without Zbtb38 lentivirus administration.…”
Section: Resultsmentioning
confidence: 99%
“…Noxa and Puma, their expression levels were decreased in Zbtb38 lentivirus-treated SCI mice from day 4 after injection, whereas Bak expression was only significantly lower on the days 2 of testing when Zbtb38 expression was rescued (Figure 5 ). Zbtb38 has been implicated to promote proliferation and G1/S transition in mouse embryonic stem cells [ 24 ]. We next determined cell cycle with or without Zbtb38 lentivirus administration.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether loss of CIBZ affects ESC differentiation, we used CIBZ knockout (CIBZ −/− ) ESC line, which was maintained in the undifferentiated state, as described previously 18 , and the effects of CIBZ knockout were determined using semi-quantitative PCR. These experiments showed no changes in Nanog, Sox2, and Oct3/4 expression in the absence of CIBZ during ESC differentiation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then demonstrated that loss of CIBZ induces apoptosis in murine cells 16 , and that CIBZ negatively regulates myogenic differentiation by binding and inhibiting the myogenin promoter via its zinc finger domains 17 . Because CIBZ is highly expressed in ESCs and is critical for ESC proliferation 18 , we hypothesized that CIBZ plays a role in the regulation of ESC differentiation.…”
mentioning
confidence: 99%
“…It was further demonstrated that, depending on the gene context, the C-terminal ZBTB38 ZFs participate in modulating transcriptional outcomes (37). These findings have significant implications for delineating the overall biological function of ZBTB38, given that its transcriptional activities have been linked to a number of core cellular processes such as cellular proliferation (38), apoptosis (35,39), and replication/genomic stability (40).…”
mentioning
confidence: 97%